2021
DOI: 10.1155/2021/8851027
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Gray Matter Volume and Functional Connectivity in Parkinson’s Disease with Rapid Eye Movement Sleep Behavior Disorder

Abstract: Objective. Rapid eye movement (REM) sleep behavior disorder (RBD) is a common symptom in Parkinson’s disease (PD), and patients with PD-RBD tend to have an increased risk of cognitive decline and have the tendency to be akinetic/rigidity predominant. At the same time, the mechanisms of RBD in patients with PD remain unclear. Therefore, this study aimed to detect the structural and functional differences in patients with PD-RBD and PD without RBD (PD-nRBD). Methods. Twenty-four polysomnography-confirmed patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…When using a seed‐based approach of a priori regions of interest based on gray matter loss in PD patients with RBD, functional connectivity was lower between the right superior occipital gyrus and posterior regions including the left fusiform gyrus, left calcarine sulcus, and left superior parietal gyrus compared to PD patients without RBD. The reduced connectivity between the superior occipital gyrus and the superior parietal gyrus positively correlated with cognition (Jiang et al, 2021).…”
Section: Functional Imaging Abnormalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When using a seed‐based approach of a priori regions of interest based on gray matter loss in PD patients with RBD, functional connectivity was lower between the right superior occipital gyrus and posterior regions including the left fusiform gyrus, left calcarine sulcus, and left superior parietal gyrus compared to PD patients without RBD. The reduced connectivity between the superior occipital gyrus and the superior parietal gyrus positively correlated with cognition (Jiang et al, 2021).…”
Section: Functional Imaging Abnormalitiesmentioning
confidence: 99%
“…The authors relate such gray matter loss to cholinergic, GABAergic, and glutamatergic neuron depletion in the promotion of REM sleep and muscle atonia (Boucetta et al, 2016). A recent study on PD patients undergoing polysomnography confirmed RBD had higher cerebellar volume compared to PD patients unaffected by RBD in the vermis IV/V, and this was found to be associated with abnormal motor behavior during REM sleep (Jiang et al, 2021). In addition, reduced gray matter volume in the right superior occipital gyrus of PD patients with RBD was negatively associated with motor severity and positively associated with memory function (Jiang et al, 2021).…”
Section: S Truc Tur Al Imag Ing Ab Normalitie Smentioning
confidence: 99%
“…The results of studies assessing structural and functional MRI (fMRI) studies are summarized, in chronological order, in Table 4 [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. These include sudies of gray matter volume (GMV), cortical thickness, diffusion tensor imaging, dorsal nigral hyperintensity (DNH), neuromelanin-sensitive structural and diffusion MRI, and functional MRI.…”
Section: Structural and Functional Magnetic Resonance Imaging (Mri) Studiesmentioning
confidence: 99%
“…Compared with PD patients without RBD and controls, patients with concomitant PD and RBD or probable RBD have shown decreased volumes in the pontomesencephalic tegmentum (location of cholinergic, GABAergic, and glutamatergic neurons), medullary reticular formation, hypothalamus, thalamus, putamen, amygdala, and anterior cingulate cortex [ 171 ], volume decrease over time in the left caudate nucleus, pallidum and amygdale [ 187 ], and a relatively high GMV in the cerebellar vermis IV/V and low GMV in the right superior occipital gyrus [ 188 ].…”
Section: Structural and Functional Magnetic Resonance Imaging (Mri) Studiesmentioning
confidence: 99%
See 1 more Smart Citation